CAPABILITY OF PAPILLOMAVIRUS INFECTION PREVENTION IN GIRLS AND WOMEN OF VARIOUS AGES - F.Ch. Shakhtakhtinskaya; M.G. Galitskaya (Педиатрическая фармакология, 2009)
The article looks at one of the critical issues in modern medicine — human papilloma virus infection. The prevalence of this infection in the world and the possibility of primary prevention in females of various age groups are highlighted in details. It provides the results of vaccine prevention against the human papilloma virus in Russian in girls and women aged 9 to 26 years.Key words: papilloma virus infection, cervical cancer, women, girls, vaccinal prevention.